Latin America and the Caribbean as they enter the twenty-first century - Burki, Shahid Javed (1996)
Notes that the region needs to breakout of the quagmire of poverty, and that this requires policy reform in at least the following six areas: competitiveness, domestic savings, infrastructure, rebuilding the state, labour market reform and educational reform.